Pengaruh Jumlah Partisipan terhadap Produktivitas dalam Diskusi Kelompok Pembelajaran - Mulyadi Guntur Waseso (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Effects of Group Size on Productivity in Learning Group Discussion. This experimental research was designed to test the productivity difference between small group, medium group, and large group in problem solving discussion. The subjects were 36 students drawn randomly, which were assigned to discuss in the three kinds of group. The group product was ideas for solving problems posed, which were then evaluated quantitatively and qualitatively by three "judges" working independently. The analyses of variance and t-test were applied to analyse data. It was found out from the data analyses that the quantity of ideas produced by the three kinds of group had no significant differences, but the solution ideas produced by the medium group (with 6 members) were highest in quality.